935. A Hospital Cluster of the Emerging Drug-resistant Yeast Saprochaete clavata. (4th December 2021) - Chan, Xin Hui S; Cubillo-Garcia, Cristina; Ali, Shanom; Gorton, Rebecca; Rhodes, Johanna; Choy, Bennett; Fisher, Matthew; Thomson, Kirsty; Gant, Vanya; Stone, Neil; Satta, Giovanni
Abstract: Background: Saprochaete clavata, an ascomycetous yeast intrinsically resistant to echinocandins, is a rare yet emerging pathogen associated with invasive infections in immunosuppressed patients, particularly those with haematological malignancies. It is commonly misidentified as the closely-related S. capitata . Outbreaks have been associated with a high mortality rate of >50%, due in part to delayed diagnosis and resistance to commonly-used antifungals. Environmental source identification is challenging, although dishwashers and milk flasks have been implicated in previous hospital clusters. Methods: We describe a cluster of five haematology-oncology patients with disseminated S. clavata infections between April 2020 and April 2021 following current or recent admissions to the same ward. Results: All had prolonged (median=24 days, range=9-210) and profound immunosuppression from chemotherapy and/or stem cell transplantation for acute myeloid leukaemia (n=3) or lymphoma (n=2) at the time of culture positivity. Four were severely neutropaenic (median=0.08/mm 3, range=0.01-0.26). Median patient age was 62 years (range=58-73). S. clavata was isolated from blood (n=3), urine (n=2), and liver tissue (n=1) samples. Whole genome sequencing of these isolates was performed to confirm the presence of an outbreak. All patients received empirical treatment with intravenous caspofungin before culture-guided therapy with intravenous liposomal amphotericin B +/- oral flucytosine. Two of the five patients died although both had advanced refractory malignancy. Detailed environmental sampling of fridges/freezers, drains, and vents in patient rooms and clean areas for handling or storage of food and medication failed to identify a clear point source despite isolation of multiple environmental organisms. No further cases have emerged after intensification of the cleaning regimen in these areas. Conclusion: Our experience highlights the emerging threat of drug-resistant yeasts particularly in the immunocompromised. Management of such outbreaks requires a multidisciplinary approach incorporating antifungal stewardship, infection control, and environmental microbiology, alongside close clinical liaison between haemato-oncologists and infection specialists. Disclosures: All Authors : No reported disclosures